Making progress: the role of cancer councils in Australia in indigenous cancer control - Thompson, S.; Shahid, Shaouli; DiGiacomo, Michelle; Pilkington, L.; Davidson, Patricia (BioMed Central Ltd, 2014)
Background: Indigenous Australians have poorer outcomes from cancer for a variety of reasons including poorer participation in screening programs, later diagnosis, higher rates of cancer with poor prognosis and poorer uptake and completion of treatment. Cancer prevention and support for people with cancer is part of the core business of the State and Territory Cancer Councils. To support sharing of lessons learned, this paper reports an environmental scan undertaken in 2010 in cancer councils (CCs) nationwide that aimed to support Indigenous cancer control. Methods: The methods replicated the approach used in a 2006 environmental scan of Indigenous related activity in CCs. The Chief Executive Officer of each CC nominated individuals for interview. Interviews explored staffing, projects, programs and activities to progress cancer control issues for Indigenous Australians, through phone or face-to-face interviews. Reported initiatives were tabulated using predetermined categories of activity and summaries were returned to interviewees, the Aboriginal and Torres Strait Islander Subcommittee and Chief Executive Officers for verification.Results: All CCs participated and modest increases in activity had occurred in most states since 2006 through different means. Indigenous staff numbers were low and no Indigenous person had yet been employed in smaller CCs; no CC had an Indigenous Board member and efforts at capacity building were often directed outside of the organisation. Developing partnerships with Indigenous organisations were ongoing. Acknowledgement and specific mention of Indigenous people in policy was increasing. Momentum increased following the establishment of a national subcommittee which increased the profile of Indigenous issues and provided collegial and practical support for those committed to reducing Indigenous cancer disparities. Government funding of “Closing the Gap” and research in the larger CCs have been other avenues for increasing knowledge and activity in Indigenous cancer control. Conclusions: This environmental scan measured progress, allowed sharing of information and provided critical assessment of progress across areas of importance for increasing Indigenous cancer control. Structured examination of policies, institutional support systems, programs and interventions is a useful means of highlighting opportunities for progress with minority groups relevant for many organisations. Progress has occurred with momentum likely to increase in the future and benefit from commitment to long-term monitoring and sharing of achievements.